Meeting the Enemy : American Exceptionalism and International Law. - Saito, Natsu Taylor (Critical America., 2010)
Since its founding, the United States has defined itself as the supreme protector of freedom throughout the world, pointing to its Constitution as the model of law to ensure democracy at home and to protect human rights internationally. Although the United States has consistently emphasized the importance of the international legal system, it has simultaneously distanced itself from many established principles of international law and the institutions that implement them. In fact, the American government has attempted to unilaterally reshape certain doctrines of international law while disrega.